Environmental, Social, and Governance (ESG) Performance, Tax Avoidance, and The Moderating Role of Finansial Constraints: An Empirical Study of Non-Financial Firms Listed on The Indonesia Stock Exchange in The Period 2019-2023 - Putri, Rezkia Nadiva; Sebrina, Nurzi (Jurnal Eksplorasi Akuntansi, 2025)
This research aims to examine the effect of ESG Performance on Tax Avoidance, with Financial Constraints as a moderating variable, in non-financial firms listed on the Indonesia Stock Exchange during the 2019 – 2023 period. By using purposive sampling, a total of 37 firms were selected as the sample. This research adopts a causal associative approach with quantitative methodology. Tax avoidance, as the dependent variable, is measured by Book Tax Differences. ESG Performance, as the independent variable, is assessed based on ESG score obtained from Refinitiv Eikon. Financial Constraints, as the moderating variable is measured using Whited and Wu index. The data were analyzed using panel data regression with EViews 12 software. The results indicate that ESG performance has no significant effect on Tax Avoidance. Futhermore, Financial Constraints do not moderate the relationship between ESG performance and Tax Avoidance.